Pengaruh Pengembangan Kawasan Transit Oriented Development (TOD) Terhadap Peningkatan Zona Nilai Tanah di Kawasan Perkotaan - Nofitri Wulan; Izzatusholekha; Zhafirah Zhafarina (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
The development of Transit Oriented Development (TOD) areas aims to improve accessibility and integration of mass transportation in urban areas. This study aims to analyze the effect of TOD development on increasing the Land Value Zone (ZNT). The method used is a literature study by analyzing 35 scientific journals and various related references, and supported by Land Value Zone (ZNT) data from Bhumi ATR/BPN in the Lebak Bulus, Blok M, and Dukuh Atas MRT areas. The results show that areas located close to MRT stations tend to have higher land values ​​than areas further away. The Blok M and Dukuh Atas MRT areas have land values ​​that are generally in the category above Rp20,000,000 per square meter, while the Lebak Bulus MRT area shows land values ​​that vary in the range of Rp5,000,000–Rp20,000,000 per square meter. The increase in land value is influenced by high accessibility, economic activity, and regional development supported by the implementation of the TOD concept. Thus, TOD development has an impact on increasing the Land Value Zone (ZNT) and can be an indicator of urban area development and a consideration in regional planning.